Roma Writings Romani Literature and Press in Central, South-Eastern and Eastern Europe from the 19th Century until World War II - Bianca Roman, Raluca (Brill, 2021)
The book focuses on the early period of Roma publishing (from the nineteenth century until the Second World War) when the first original texts, fiction and media publications authored by Roma appeared.Based on extensive archival and historical research, including the discovery of earlier, up to now unknown sources, the literary activities of Roma in Central, South-eastern and Eastern Europe are discussed in their historical context and interrelation with the birth of the Roma emancipatory movement. Romani literature and press are thus embedded in the history and literary studies of the European national literatures.The authors: Raluca Bianca Roman, Sofiya Zahova, Aleksandar G. Marinov, Elena Marushiakova and Vesselin Popov are affiliated with the University of St Andrews, UK. Other authors are Tamás Hajnáczky (Károli Gáspár University of the Reformed Church in Hungary), Viktor Shapoval (Moscow City University, Russia), and Risto Blomster (Finnish Literature Society/ The Finnish Cultural Foundation).